P61 Respiratory ill health in the silica exposed brick manufacturing sector. (12th November 2015) - Fishwick, D; Sumner, J; Barber, CM; Robinson, E; Codling, A; Lewis, L; Young, C; Warren, N
Abstract : Introduction: Exposure at work to inhaled respirable crystalline silica (RCS) has previously been linked with silicosis, tuberculosis, lung cancer and COPD. Whilst the risk of developing silicosis is largely a function of cumulative lifetime RCS exposures, current workplace exposures contribute to this risk. Methods: A cross sectional GB based workplace study of brick manufacturers was carried out, in order to identify a subsequent longitudinal cohort. Participating worksites were using silica to make bricks for various uses. Consenting workers were asked to complete an interviewer led questionnaire, undergo lung function testing and complete a full occupational history including details of lifetime exposure to RCS. Consenting workers had a PA Chest Radiograph using a mobile facility, and levels of RCS exposure in the personal breathing zone were taken. Results: 189 workers took part, with a mean age of 45.9 years and 22 years median (range 0.08–47) years worked overall in industry. Three had radiological evidence of silicosis (ILO standards used; 2 definite and one probable case). Respiratory symptoms were common; for example 14.3% reported cough, 21.2% wheeze in the last 12 months, 14.3% reported ever having asthma. 13.2% reported at least one work related respiratory symptom. Mean lung function values were as follows; mean (SD) percentage predicted FEV1 98.1 (15.2) and FVC 102.4 (13.9). Fourteen workers had measured airways obstruction (as defined by an FEV1 /FVC <0.7); in this cross sectional analysis its presence did not significantly relate to current smoking status or lifetime duration of RCS exposure, although was significantly associated with an increased time worked in the current work area. Airways obstruction was also associated with the reporting of a diagnosis of (ever having) asthma and wheeze in the last 12 months. Conclusions: This cross sectional study of silica exposed brick workers has identified a cohort for longer term follow up. Future work will allow the development of dose response relationships, corrected for other relevant factors, between cumulative RCS exposure and FEV1 decline and will assist in the development of workplace interventions to reduce the health risks associated with RCS exposure in this group of workers.